PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MENGGUNAKAN MODEL POLYA PADA MATERI KUBUS DAN BALOK - Madubun, Fenty Madelin; Laurens, Theresia; Gaspersz, Magy (Jurnal Pendidikan Matematika Unpatti, 2022)
The ability to solve problems is the main goal in the educational process, including mathematics. Based on previous studies, it was found that the problem solving of students' problems was not as expected. One of the learning methods that can be used is the Polya model problem solving method. The purpose of this study was to improve problem solving skills using the Polya model on cube and cuboids material for class VIII students of SMP Negeri 1 Tual. This type of research is classroom action research (CAR) which consists of three cycles, with each cycle consisting of two meetings. The subjects in the study were students of class VIIIa-3 SMP Negeri 1 Tual with a sample of 14 students. Data collection techniques in this study were observation and tests. The data analysis technique used is qualitative and quantitative data analysis techniques. Based on the results, it can be concluded that: (1) There is an increase in the problem solving ability of students using the Polya model (2) the errors made by students related to problem solving abilities in the Polya model are errors in the processing and conclusions. Based on the results obtained, it can be said that there is an increase in problem solving abilities using the Polya model